2021
DOI: 10.1126/sciadv.abc2962
|View full text |Cite
|
Sign up to set email alerts
|

Heating events in the nascent solar system recorded by rare earth element isotopic fractionation in refractory inclusions

Abstract: Equilibrium condensation of solar gas is often invoked to explain the abundance of refractory elements in planets and meteorites. This is partly motivated, by the observation that the depletions in both the least and most refractory rare earth elements (REEs) in meteoritic group II calcium-aluminum–rich inclusions (CAIs) can be reproduced by thermodynamic models of solar nebula condensation. We measured the isotopic compositions of Ce, Nd, Sm, Eu, Gd, Dy, Er, and Yb in eight CAIs to test this scenario. Contrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 58 publications
6
65
1
Order By: Relevance
“…The fg-CAIs were chosen for their relatively primitive characteristics. In general, they display condensate-like petrographic features (25), have never been melted, and their chemical compositions match those predicted by equilibrium thermodynamic calculation for partial condensation from a gas of solar composition gas [e.g., (26)(27)(28)(29)]. Our samples (figs.…”
Section: Introductionsupporting
confidence: 72%
“…The fg-CAIs were chosen for their relatively primitive characteristics. In general, they display condensate-like petrographic features (25), have never been melted, and their chemical compositions match those predicted by equilibrium thermodynamic calculation for partial condensation from a gas of solar composition gas [e.g., (26)(27)(28)(29)]. Our samples (figs.…”
Section: Introductionsupporting
confidence: 72%
“…Of these, Lee and Tanaka [10] detected a possible Eu isotope fractionation in geological samples. Hu et al [11] also reported Eu isotope ratio variation from meteorite samples and mentioned that Eu isotopic variations correlate with mass-dependent Sr isotopic variation. However, in this study, we noticed that there might occur pseudo-Eu fractionation due to a trace of Gd matrix in purified Eu fraction from geological materials.…”
Section: Comparison Of Eu Isotope Ratio Estimates From Geochemical Reference Rocksmentioning
confidence: 98%
“…Previous studies have established Eu isotope ratio results for geological materials and some meteorites using MC-ICP-MS [4,[9][10][11]. Of these, Lee and Tanaka [10] detected a possible Eu isotope fractionation in geological samples.…”
Section: Comparison Of Eu Isotope Ratio Estimates From Geochemical Reference Rocksmentioning
confidence: 99%
“…The vast majority of CAIs formed 4567.2 ± 0.2 Ma ago, over a period of ~40,000 to 200,000 years (17)(18)(19)76), possibly while the Sun was in transition from the protostellar into a pre-main sequence (T Tauri) phase of star formation (77). The 26 Al/ 27 Al systematics of bulk CAIs suggests that the formation of 26 Al-rich refractory inclusions was a punctuated and recurrent process, possibly associated with episodic flare-ups, in the form of FU-Orionis and EX-Lupi outbursts [e.g., (61,78,79)). Larsen et al (80) proposed that CV CAIs could have formed on the time scale of <8000 years via chemical processing of 26 Al-rich presolar carriers in a hot zone proximal to the proto-Sun (<0.1 AU).…”
Section: Cosmolocation Of the Cai Factorymentioning
confidence: 99%